False positive : a novel - Grant, Andrew, 1968- (2015)
"It's a desperate race against the clock. Detective Demonbruen and his temporary partner, Jan Loflin, seek a missing six-year-old foster child. Demonbruen, himself a survivor of the foster system, is haunted by his own brutal childhood and the death of his father. He labors under a cloud of suspicion, determined to find the missing boy before it's too late. But are his motives really pure? His record is a minefield of red flags and question marks: how is a Birmingham cop able to afford a Porsche, a penthouse, and a summer cabin? Why does he have so much success with the petty criminals who form his network of confidential informants? And is there a legitimate explanation for the multiple excessive-force complaints on his jacket?"--
Keywords: Police -- Alabama -- Birmingham -- Fiction; Missing children -- Fiction; FICTION / Suspense; FICTION / Thrillers; FICTION / Mystery & Detective / General; Suspense fiction